SEJARAH KEPEMILIKAN HUTAN KEMENYAN PANDUMAAN DAN SIPIHUTA KECAMATAN POLLUNG, HUMBANG HASUNDUTAN - Roki (Magister Hukum Universitas HKBP Nommensen, 2024)
In 2019 for the first time held simultaneous elections. Voter turnout in this election includes millennial. Some of the millennial are at university. Therefore, it is necessary to know the role of universities in the 2019 general election. The research was conducted with statute approach, case approach, historical approach, comparative approach, and conceptual approach. From this research, it can be found that universities have sought to increase millennial voter participation in the 2019 general election by including material on elections in courses as well as conducting public lectures.